2019
DOI: 10.1515/znc-2019-0123
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of tuliposides D and F from tulip cultivars

Abstract: Abstract6-Tuliposides A (6-PosA) and B (6-PosB) are major defensive secondary metabolites in tulip cultivars (Tulipa gesneriana), having an acyl group at the C-6 position of d-glucose. Although some wild tulip species produce 1,6-diacyl-glucose type of Pos (PosD and PosF), as well as 6-PosA/B, they have not yet been isolated from tulip cultivars. Here, aiming at verifying the presence of PosD and PosF in tulip cultivars, tissue extracts of 25 cultivars were analyzed by high-performance liquid chromatography (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, the identification of PosG, which occurs only in bulbs at low levels, suggests the possibility of the presence of as yet undiscovered minor Pos species that may occur in a tissue-and/or growth stage-specific manner. By using a reaction catalyzed by TgTCEs (TgTCEA and TgTCEB) that function regiospecifically to remove the acyl group at the C-6 position of Pos irrespective of the presence of a substituent at the C-1 position [8,16], we succeeded in the identification of PosD and PosF as minor Pos in limited tissues of a few tulip cultivars [15]; these Pos were known to be present at considerable levels in wild species [4,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the identification of PosG, which occurs only in bulbs at low levels, suggests the possibility of the presence of as yet undiscovered minor Pos species that may occur in a tissue-and/or growth stage-specific manner. By using a reaction catalyzed by TgTCEs (TgTCEA and TgTCEB) that function regiospecifically to remove the acyl group at the C-6 position of Pos irrespective of the presence of a substituent at the C-1 position [8,16], we succeeded in the identification of PosD and PosF as minor Pos in limited tissues of a few tulip cultivars [15]; these Pos were known to be present at considerable levels in wild species [4,14].…”
Section: Discussionmentioning
confidence: 99%
“…PosD has the 6-PosA-type acyl group at both the C-1 and C-6 positions of d-glucose, and PosF has the 6-PosA-type acyl group at the C-1 position and the 6-PosB-type acyl group at the C-6 position. Recently, we reported that some tulip cultivars can also produce PosD and PosF, although the number of cultivars having PosD and PosF was limited and the amount of PosD/PosF was much lower than that of the major Pos, 6-PosA and 6-PosB [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation